Sinergi Chat GPT dan Kecerdasan Emosional dalam Dunia Pendidikan “Menjembatani Potensi Transformatif untuk Perkembangan Manusia” - Graha Pratiwi, Rezky; Poniman; Yuliansyah (Direktorat Riset dan Pengabdian Masyarakat Universitas Bina Darma Palembang, 2024)
This study aims to investigate the synergy between Chat GPT and emotional intelligence in the context of education and the transformative potential revealed in human development by providing an in-depth understanding of the benefits and implications of using this combination. The use of Chat GPT as an adaptive artificial intelligence tool and emotional intelligence involving understanding and managing emotions shows promising results in improving students' self-understanding, empathy, critical thinking skills, and communication skills. In addition, this synergy also encourages inclusivity and diversity in learning. This study was conducted through a qualitative approach involving student participants. Data were collected through classroom observations, interviews, and document analysis to gain insight into students' experiences and the impact of this synergy in human development. The results show that the synergy between Chat GPT and emotional intelligence has transformative potential in shaping a generation with a deeper understanding of themselves, strong critical thinking skills, effective communication skills, and sensitivity to cultural differences. These findings provide important implications in the context of holistic education